Le droit d’avoir migré : Émergence et constitution du mouvement des braceros (Journaliers agricoles mexicains aux États-Unis, 1942-1964) - Philippe Schaffhauser (IdeAs)
This article examines the issue of the deferred social recognition of the experience of migrant workers by positing the following question: to what degree, and in what conditions, does this experience create social rights for the individuals who lived it? The act of social recognition, and the construction and application of rights related to it, are far from established principles, for it is hardly natural to legitimize the existence of migrant workers through political and institutional pathways that lead to granting them a specific status. This problem is explored through an analysis of the bracero movement in Mexico (Bracero Program, 1942-1964), and recent protests over the lack of recognition and the failure to pay pensions from a fund established in the terms of the original bracero agreement to the workers involved when they reached retirement age. The several particularities of this social struggle enrich our understanding of contemporary social movements in relation to such topics as senior citizens living in conditions of social vulnerability, and the world of Mexico’s countryside. Based on fieldwork conducted in the states of Michoacán and Zacatecas, and in Mexico City, the paper articulates the original questions and presents early results.